Copyrights Protections of Songs In Cover Version Activities - Santina, Rika; Santiago, Faisal; Barthos, Megawati (Green Publisher Indonesia, 2023)
A phenomenon that is currently rife is covering songs created by other people to be uploaded on digital music media for commercial purposes without the creator's permission. While copyright violations have occurred so far, often without any meaningful legal settlement. One of the most visited digital music platforms by the public is a video-based digital music media called YouTube. The results are not copyright infringement if the creation and distribution of the Cover Version through information and communication technology media is non-commercial in nature and benefits the Author or related parties, if the Author expresses no objection to such production and distribution. If the act of covering a song does not meet the elements of Article 43 and Article 44, it is a Copyright infringement. What Gen Halilintar did was copyright infringement, because he made a cover of a song without fulfilling the above elements. The author does not fully agree with the judge's decision to completely reject Nagaswara's lawsuit, because what Gen Halilintar did was a copyright infringement. The basis for the judge's consideration was that the purpose of making cover came from subscribers. Many people cover songs through YouTube, Gen Halilintar covered Nagaswara's “Lagi Syantik” song without permission but still included the word cover and the song title. The judge found that the claim for royalties from this song fell to Wahana Musik Indonesia (WAMI) as the collective management agency, not to Gen Halilintar